The Factors that Affecting Community’s Behavior Using Contaminate and Pleonasm Language Errors on Facebook Shopping Group Online: Sociolinguistic Study - Lia Indriani Tobing; Mhd. Pujiono; Rozanna Mulyani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Language errors caused miscommunication or misunderstanding so that the message cannot well delivered. Pleonasm language errors are the use of excessive words and it can cause a language shift that is when language abnormalities affect the meaning of the language. The purpose of this study is to analyze factors that influence community's behavior in using language errors on facebook accounts of online shopping group based on sociolinguistic studies. This research is a type of mixed method research.The data in this study are words, phrases and sentences that contain pleonasm and contamination. Data sourced from netizens' uploads and comments in the online shopping group. Data collection is done by using substitution. The data were analyzed using Miles, Huberman and Saldana interactive model analysis techniques. Based on the results of the study found as many as 30 (5 forms of words, 20 forms of phrases and 5 forms of sentences), there were 11 contaminations (3 forms of words, 5 forms of sentences and 3 forms of phrases). There are as many as 99 forms of language errors consisting of 30 errors in the form of Lapses, 30 errors in the form of errors, 30 forms of errors in the form of mistakes. The factors that influence language errors such as mother tongue factors, age factors, motivational factors and habits, and environmental factors.